(untitled) (Medico Legal Update, 2020)
Efforts so that a person’s nutritional needs can be obtained optimally is by holding a food that is managed by applying various scientific disciplines. This study aims to analyze the food delivery system and the level of satisfaction of students in Tebuireng Islamic Boarding School in Jombang, East Java. This research was observational with a cross-sectional study design. Samples taken are students who live and or boarding at Tebuireng Islamic Boarding School in Jombang, East Java, with a total of 303 people from the class 2 population. Samples were taken using total sampling. Data collection is done by providing an identity questionnaire, satisfaction test form sheets and interviews with foodservice parties. The results showed that the food delivery system at Tebuireng Islamic Boarding School in Jombang in East Java was already good in management, service, and workflow but there were still shortages, such as the proportion of students and catering service staff that was not appropriate, there was no calculation of individual student needs, and food handlers hygiene knowledge still needs to be improved. The level of satisfaction of students to the overall menu of students with a thin nutritional status of 76.36% with the category “Satisfied”; students with normal nutritional status of 67.79% with the category “Dissatisfied”; and students with fat nutritional status of 64.49% with the category “Dissatisfied”. Training regarding sanitation and hygiene is good and right during the process of providing food and training on how to process various kinds of menus from one food item.